Optoelectronic properties of 2D heterojunction ZrO2– MoS2 material using first-principles calculations. (August 2021) - Patel, V.R.; Patel, Abhishek; Sonvane, Yogesh; Thakor, P.B.
Abstract: In the present work, the structural, electronic, and optical properties of heterojunction ZrO2 –MoS2 have been investigated based on first-principles calculations. The heterojunction ZrO2 – MoS2 has an indirect bandgap of 1.66 eV and a direct bandgap of 1.88 eV, which describes its semiconducting nature. The heterojunction ZrO2 –MoS2 has a lower bandgap than the components monolayer ZrO2 and MoS2 . The optical properties of heterojunction ZrO2 –MoS2 along with monolayers ZrO2 and MoS2 are systematically investigated. The optical properties of heterojunction ZrO2 –MoS2 have in the visible to ultraviolet region. The result suggests the heterojunction ZrO2 –MoS2 material for nanoelectronics and optoelectronic applications. Highlights: First report on the electronic and optical properties of the 2D heterojunction ZrO2 –MoS2 . The heterojunction ZrO2 –MoS2 shows semiconducting nature with reduced indirect bandgap of 1.66 eV. High Absorption coefficient of the order 10 5 cm −1 in visible to ultraviolet region. Desirable electronic and optical properties of heterojunction ZrO2 –MoS2 for the optoelectronic applications.